Bencene and alcohols from occupational exposure in graphic arts in Bucaramanga, Colombia - Ramírez Oliveros, Erika Patricia; Rangel Pico, Angélica Nohemy; Zambrano Valdivieso, Óscar Javier (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
In Colombia, the publishing industry, known as graphic arts, includes periodical and commercial publications, books and packaging, among others. This study carried out a sample of exposure to bencene, 2-propanol and n-propanol in workers in the sector. Sample analysis used method 1501 of the National Institute for Occupational Safety and Health (NIOSH, 1984). The results show the presence of organic vapours of bencene and alcohols. Other substances such as xylene and toluene are likely to be present in these environments. Likewise, it concludes that the analysis of other alcohols such as ethanol, isobutanol and butanol should be considered.